Stock markets, credit markets, and technology-led growth - Brown, James R.; Martinsson, Gustav; Petersen, Bruce C. (Journal of Financial Intermediation, 2017)
The high-tech sector accounts for the majority of corporate innovation in modern economies. In a sample of 38 countries, we document a strong positive relation between the initial size of the country's high-tech sector and subsequent rates of GDP and total factor productivity growth. We also find a strong positive connection between a country's equity (but not credit) market development and the size of its high-tech sector. Our main difference-in-differences estimates show that better developed stock markets support faster growth of innovative-intensive, high-tech industries. The main channels for this effect are higher rates of productivity and faster growth in the number of new high-tech firms. Credit market development fosters growth in industries that rely on external finance for physical capital accumulation but is unimportant for growth in innovation-intensive industries. These findings show that stock markets and credit markets play important but distinct roles in supporting economic growth. Stock markets are uniquely suited for financing technology-led growth, a particularly important concern for advanced economies.